Development and validation of the pre-match anxiety scale for college futsal players (PMAS-CFP) - Hardiansyah, Sefri; Hasibuan, Noval Pratama; Blegur, Jusuf; Syahriadi (UIR Press, 2025)
Background: Anxiety is a major psychological factor that significantly affects the performance of college futsal players, so coaches need to understand anxiety. However, existing anxiety scales are not explicitly developed for futsal and often overlook critical pre-match external stressors, such as the opponent’s reputation and audience pressure, which are highly influential in the futsal environment. As a result, pressure in these areas is still ignored. Objective: To develop an instrument that can measure the pre-match anxiety scale for college futsal players (PMAS-CFP). Methods: This study employed an R&D design, incorporating content validity, ICC testing, construct validity, and reliability testing. Fourteen items were designed using three indicators: concentration impairment, somatic anxiety, and worry. Findings/Results: Psychometric testing showed strong content validity (Aiken’s V = 0.67-0.96), acceptable ICC (0.550), adequate construct validity (factor loadings = 0.60-0.82), high internal consistency (Cronbach’s α = 0.922), good CFA loadings (0.667-0.946), composite reliability (CR = 0.965), and average variance extracted (AVE = 0.681). A total of 13 items met the required validity and reliability standards, consisting of concentration disorders (3 items), somatic anxiety (5 items), and worry (5 items). Conclusion: The PMAS-CFP is a valid and reliable tool for assessing pre-match anxiety in college futsal players, filling a gap in existing non-sport-specific anxiety measurements. This scale can help sports psychologists and coaches monitor athletes’ psychological readiness. Future studies are recommended to expand the use of this tool during and after matches, as well as to validate its use at broader levels of competition.